Laws and Ordinances Governing the City of Chicago 88-89 (1873) - (:unkn) unknown (My University, 1873)
Part I, Ch. 31, § 6,: Forbade all persons from carrying firearms or throwing stones or other missiles within any public park.
Keywords: CARRY - CERTAIN PUBLIC PLACES